Examining the moderating role of technostress and compatibility in EFL Learners’ mobile learning adoption: A perspective from the theory of planned behaviour - Wang, Qiong; Zhao, Guoqing; Cheng, Zhuo (Frontiers in Psychology, 2022)
Mobile English learning has multiple advantages and brings enormous benefits to EFL learners. However, not everyone adopts it, and the determinants of learners’ adoption intention have not yet been investigated fully. This study aimed to better understand learners’ adoption by employing the theory of planned behaviour (TPB) in conjunction with the influences of technostress and compatibility. Based on existing literature, a research model was proposed and verified with a sample of 409 undergraduates from a Chinese university. The results indicated that in the context of mobile English learning: (a) Individuals with higher adoption intention are more likely to engage in mobile English learning with higher frequency (b = 0.473, P < 0.001) and longer duration (b = 0.330, P < 0.001); (b) Individuals’ attitude toward mobile English learning (b = 0.171, P < 0.05), perceived behavioural control (b = 0.221, P < 0.001), subjective norms (b = 0.237, P < 0.05), and compatibility (b = 0.443, P < 0.001) are significantly positively associated with their adoption intention; (c) Compatibility is the strongest predictor of adoption intention (b = 0.443, P < 0.001) and negatively moderates the effect of subjective norms on adoption intention (b = –0.103, P < 0.005); (d) The influence of technostress on the adoption intention of mobile English learning is not significant (b = –0.041, P > 0.05). Practical implications related to mobile English learning were discussed.